Exploring genotype‐phenotype relationships in the CDKL5 deficiency disorder using an international dataset. Issue 1 (20th October 2020) - MacKay, Conor I.; Wong, Kingsley; Demarest, Scott T.; Benke, Tim A.; Downs, Jenny; Leonard, Helen
Abstract: Characterized by early‐onset seizures, global developmental delay and severe motor deficits, CDKL5 deficiency disorder is caused by pathogenic variants in the cyclin‐dependent kinase‐like 5 gene. Previous efforts to investigate genotype‐phenotype relationships have been limited due to small numbers of recurrent mutations and small cohort sizes. Using data from the International CDKL5 Disorder Database we examined genotype‐phenotype relationships for 13 recurrent CDKL5 variants and the previously analyzed historic variant groupings. We have applied the CDKL5 Developmental Score (CDS) and an adapted version of the CDKL5 Clinical Severity Assessment (CCSA), to grade the severity of phenotype and developmental outcomes for 285 individuals with CDKL5 variants. Comparisons of adapted CCSA and CDS between recurrent variants and variant groups were performed using multiple linear regression adjusting for age and sex. Individuals with the missense variant, p.Arg178Trp, had the highest mean adapted CCSA and lowest mean developmental scores. Other variants producing severe phenotypes included p.Arg559* and p.Arg178Gln. Variants producing milder phenotypes included p.Arg134*, p.Arg550*, and p.Glu55Argfs*20. There are observed differences in phenotype severity and developmental outcomes for individuals with different CDKL5 variants. However, the historic variant groupings did not seem to reflect differences in phenotype severity or developmental outcomes as clearly as analyzed by individual variants. Abstract : This study is the first exploration of genotype‐phenotype relationships for 13 recurrent variants in CDKL5. We also re‐examined the historic variant groupings previously used to investigate variants for the CDKL5 deficiency disorder. By applying two recently developed measures, we demonstrated that p.Arg178Trp, p.Arg559* and p.Arg178Gln variants produce severe phenotypes while variants producing milder phenotypes included p.Arg134*, p.Arg550* and p.Glu55Argfs*20. Our novel findings highlight the need for continued international collaboration between research groups to facilitate large study sizes and meaningful results for rare genetic conditions like the CDKL5 deficiency disorder.